Meta-Subject Potential of a Foreign Language in Teaching Natural Disciplines at a Pedagogical University - Kabbassova, Ainagul; Shakarmanova, Maizhan; Temerbayeva, Zhanna; Bulyga, Leonid; Sakenov, Janat (International Journal of Education and Practice, 2021)
Teaching a foreign language in the process of preparing future teachers is guided by the needs of the modern school system, in which reforms are being actively implemented. The meta-subject approach at school serves as the basis for planning learning outcomes. For example, in biology, foreign language, and physics classes, students are not only expected to know the laws and principles of a particular field of science but also to be able to embed this knowledge into an integral system of worldviews. The implementation of the idea of tri-lingualism in school education increases the role of a foreign language in the cognitive process of students. When using the meta-subject approach, English serves not only the communication needs but also for contributes in the development of meta-cognitive processes. The study of natural disciplines in Kazakh pedagogical universities is carried out not only in the Kazakh and Russian languages, but also in English. Future teachers of biology, chemistry, mathematics, and physics ought to master the basics of the natural sciences and methods of teaching them, by using the knowledge of a foreign language as a source of relevant scientific facts. This article analyzes the possibilities of a meta-subject approach in the practice of teaching a foreign language to future teachers of natural sciences. By substantiating the concept of the meta-subject potential of a foreign language, the main categories associated with meta-cognition through diagnosing students' readiness to use these ideas, one can build a foreign language education program for future teachers.